Interlanguage as An Oral Communication Strategy Used by The First Graders of The English Education Study Program of STKIP PGRI Pacitan - Rahayu, Dwi (Jurnal Penelitian Pendidikan, 2023)
This study describes the communication strategies in English used by first-level students of the English Education Study Program at STKIP PGRI Pacitan which can be seen in their interlanguage production. The research data is in the form of interlanguge which they produce when performing oral communication. Data collection techniques are elicitation and documentation. Data were analyzed qualitatively. The results of the study show that there are three main types of communication strategies used by learners, namely: over-generalization, first language transfer, and simplification. This strategy is intended by students to maintain that communication using English as the target language can continue with the limitations of their language skills. The implication of this research is that mistakes are an inevitable process in the process of learning a foreign language, so it needs to be addressed positively. Appropriate training needs to be provided to learners so that they better understand the differences between the target language and their mother tongue so as to help them develop their interlanguage system.